Belarusian adjectives-paronyms with the root asob- as the objects of the historical lexicology (based on the material of the literary language of the 1910–30s) - Zaprudski, Siarhiej M. (Journal of the Belarusian State University. Philology, 2019)
The article deals with the history of usage of adjectives with the root asob- in the Belarusian literary language of the 1910–30s. They form two paronymic sets in the modern Belarusian: asabovy – asabisty – asablivy and asobny – asoby. We come to the conclusion that the semantic opposition that became a foundation for the formation of these sets had not been fully formed by the 1930s. The word asabovy was often used as a doublet of asabisty, and the lexeme asabisty – in the meaning of asablivy. The use of the forms asablivy, asobny, asoby was more or less stable, however, in contrast to the modern usage, in the 1920s the forms asabisty, asabovy, and asobny were used in the meaning ‘different from usual’ together with the word asablivy. The deficient differentiation of the words asabovy, asabisty, asablivy and asobny did not lead to the corruption of the meaning of the utterances. Polish and Ukrainian influenced the composition of this word group inclusive with derivative nouns and adverbs. The words asabovy, asabistasć, and apparently asobnasć were borrowed from these languages; and the lexeme asobienny, borrowed from Russian, later went out of usage. Several circumstances, including the interchangeability of the forms asabovy and asabisty in the 1920s; the use of the forms asabovy, asabisty, asobny by the best writers in the non-typical meanings for the modern practice; the complexity to define exact meanings in a range of usage, as well as other circumstances bring us to the conclusion that the forms asabovy, asabisty, asablivy, asobny were word-formation and/or lexical and semantic variants of the same word in the 1930s rather than independent words, with their intrinsic strict meanings.
Keywords: paronyms; historical lexicology; Belarusian literary language; 1910–30s; semantic differentiation; word-formation variants; paronymic attraction